Cultural Warfare Redux: Salman Rushdie’s Knighthood - Mendes, Ana Cristina (2010)
On June 16th 2007, on the occasion of Queen Elizabeth II 80th birthday honours, it was announced that Salman Rushdie was to be conferred a Knight Bachelor by the reigning monarch for his services to literature. The bestowment of this honour upon the writer to recognise his outstanding achievement in the field of literature incited, without delay, much outrage in countries with Muslim majority populations. The Knighthood provoked nearly as much outrage as the Rushdie affair part I of nearly two decades before, when the Iranian religious leader Ayatollah Khomeini issued a fatwa, or death warrant, against the writer for supposedly blaspheming Islam in his novel. In the eyes of irate Islamists, Britain’s decision to honour the so-called “blaspheming apostate” was hence understood as a jingoistic ploy, coldly calculated to incite antagonism in the Muslim world. This essay is built on the premise that Rushdie’s Knighthood might be addressed within the framework of a renewed nostalgia for an imagined British community, and hence construed as a symptom of postcolonial melancholia.